عمل المرأة محكمة في نظام التحكيم السعودي: The Work of A Woman as An Arbitrator in The Saudi Arbitration Regulation - Alanaz, Jumaah Awwad K; Buang, Ahmad Hidayat; Daud, Mohd Zaidi (Online Journal of Research in Islamic Studies, 2021)
The Islamic Shariah acknowledges arbitration and recognizes it as having the same obligation that the rule of judge has. The legality of arbitration can be found in the text of the Quran and the Sunnah as well as in the practice of the companions, may Allah be pleased with them. However, the Islamic jurists (the fuqaha) have different opinions about the work of a woman. Some support it and others oppose it. The cause of the difference can be traced back to fiqh adjusting and the disagreement of the jurists may God have mercy on them on understanding texts or its interpretation or the achievement of it the rule of blocking the pretense. The disagreement of jurists about this issue is not new and it is existing today. With enactment of the Saudi arbitration regulation in the year of 1433H, this issue raised again because the regulator did not mention the gender of the arbitrator among the conditions. This leads to the existence of different views about this issue as the Shariah is the source of the regulation in the Saudi Arabia and there is various legal opinions about this issue in the Shariah. What is the preponderant saying of the jurists’ opinions? If a woman becomes an arbitrator, does the arbitration be null and then not be executed? From here, the study of this issue and knowing its rule in the Shariah and the regulation are important. To achieve this, the researcher divided the study into thee chapters commencing with the definition of arbitration and its nature in the first chapter. The researcher discusses in the second chapter the work of a woman as an arbitrator in the Shariah with mentioning the preponderant opinion about the issue in the writer view. In the third chapter, the writer discussed the work of a woman as an arbitrator in the perspective of the Saudi regulation and judiciary. The researcher found some results and proposed some recommendations. From the most importance of these results is that the work of a woman as an arbitrator is a controversial issue in the Islamic fiqh and the writer preponderated its permissibility. Moreover, the cause of the difference between jurists about the work of a woman results from their different understanding of the legal evidence and its legal adjusting of the issue, as well as the expansion or narrowing in the use of the rule of blocking the pretense. Add to this, the fact that the Saudi regulator did not mention the gender of the arbitrator in the conditions neither in the arbitration regulation nor in its executive regulations. This issue is important as the Saudi implemented the Shariah and has an independent judicial system. Accordingly, the researcher recommends inserting an explicit provision in the Saudi arbitration regulation talking about the working of a woman as an arbitrator and not leaving this matter to ijtihad and controversial opinions as this could act as a hindrance to the execution of judgments of the arbitrators.